Associations’ involvement in preserving and developing local communities in rural areas - Ibsen, Bjarne; Iversen, Evald Bundgård (Politica, 2024)
How much do associations in rural districts involve themselves in the local community, and what can explain differences their involvement? The analysis of this issue is based on data from a survey in 2022 of all types of associations in four rural municipalities. The analysis, which is inspired by theories of new institutionalism, shows that most associations are involved in tasks that aim to preserve or develop local conditions and institutions, and that the associations have a positive attitude towards contributing to develop the local community. The associations’ involvement in the local community depends in particular on the number of inhabitants in the local community, what their primary goals are and their size, while the associations’ age, municipal context and public support have little significance.